Model Panel Regression : Pengaruh Economic Value Added (Eva), Market Value Added (Mva), Kebijakan Dividen Dan Kepemilikan Manajerial Terhadap Nilai Perusahaan Food And Beverage Di Bursa Efek Indonesia (Bei) - Ahmad Sani; Irawan Irawan (CERED Indonesia Institute, 2021)
This study aims to determine the effect of Economic Value Added (EVA), Market Value Added (MVA), Dividend Policy and Managerial Ownership on Firm Value in Manufacturing Companies in the Food and Beverage sector listed on the Indonesia Stock Exchange for the 2015-2019 period. Data was collected by the documentation method. Sample selection using purposive sampling and obtained 14 companies. Hypothesis testing was carried out using panel data regression analysis. The results of this study indicate: Economic Value Added (EVA) has a significant effect on Firm Value; Market Value Added (MVA) has a significant effect on Firm Value; Dividend policy has a significant effect on firm value; managerial ownership has a significant effect on firm value. Changes that occur in the sample company sample of 30.72% are caused by Economic Value Added (EVA), Market Value Added (MVA), Dividend Policy and Managerial Ownership; while the remaining 69.28% is determined by other variables not listed in this study.